Etika Komunikasi Digital bagi Generasi Z; Bagaimana Etika komunikasi Digital yang Baik Bisa Mengangkat Brand Dirimu - Roos Yuliastina; Isyanto ,; Ida Syafriani (Fakultas Sosial dan Ilmu Politik Universitas Wiraraja, 2026)
This community service activity aims to educate Generation Z on the importance of digital communication etiquette (netiquette) and its relationship to personal branding and brand image. The participants in this initiative are students at SMAN 1 Bluto, Sumenep Regency, who represent today’s active social media users. The methods used in this program include interactive presentations, group discussions, and real-world case studies related to digital footprints. The results of this activity demonstrate a significant increase in digital awareness among the students. Participants were able to understand that online activities have a real impact on their personal and professional reputations in the future. Additionally, students were equipped with an understanding of how ethical online communication can support the value of a brand or digital business. The high level of enthusiasm from the participants indicates the program’s success in fostering a healthier and more productive digital environment within the school setting. At the conclusion of the activity, the community service team emphasized that netiquette education grounded in personal branding is crucial for Gen Z to cultivate a culture of digital citizens who are intelligent, ethical, and ready to compete in the modern era.